Impact of Treatment Modalities on Prognosis in Patients With Renal Collecting Duct Carcinoma: A Population-Based Study - Qian, Xiaoyuan; Xu, Jinzhou; Liu, Chenqian; Zhong, Mingliang; Hong, Senyuan; Qian, Can; Zhu, Jianning; Zhang, Jiaqiao; Wang, Shaogang (Frontiers in Oncology, 2022)
Objective Renal collecting duct carcinoma (CDC) is an extremely rare disease with few studies, and the current understanding of its prognosis is limited. We used the Surveillance, Epidemiology, and End Results (SEER) registry data to explore the prognostic factors and effect of treatment modalities on the overall survival (OS) and cancer-specific survival (CSS) in patients with CDC. Methods Patients’ information of CDCs diagnosed by pathological examination between 2000 and 2018 was extracted from the SEER database. The Kaplan–Meier method was used to calculate OS and CSS and log-rank tests to evaluate the differences in OS and CSS. The associations between clinicopathological variables and survival outcomes were assessed with the Cox proportional hazard model. A directed acyclic graph (DAG) was drawn to recognize confounding factors and to obtain the multivariable regression model, and the impact of surgery, radiotherapy, and chemotherapy on OS and CSS was analyzed, respectively. Results A total of 242 patients with CDC were enrolled. The median OS and CSS time were 17 and 21 months, respectively. The OS rates at 1, 2, and 5 years were 56.9%, 41.9%, and 30.0%, respectively, while the CSS rates at 1, 2, and 5 years were 60.1%, 47.5%, and 34.8%, respectively. Patients who had a large tumor size, poor pathological grade, and advanced TNM classification exhibited worse survival outcomes. Univariable and multivariable Cox regression analyses revealed that surgery, chemotherapy, T stage, N stage, and M stage were independent prognostic factors for OS and CSS. The DAG-guided multivariate Cox regression model revealed that surgery and chemotherapy improved OS and CSS. Conclusions CDC is an exceedingly rare disease and has malignant behavior. Most patients have a high pathological grade and advanced TNM stage at diagnosis and exhibited poor survival. Resection of all visible tumors including metastatic lesions or chemotherapy can be beneficial to prognosis, while healthier benefits are less likely to receive radiotherapy. More relevant studies with larger samples are needed to verify the value of surgery and adjuvant therapy in the treatment of CDCs.